2000
DOI: 10.1002/1096-9071(200011)62:3<383::aid-jmv11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Picornavirus proteins share antigenic determinants with heat shock proteins 60/65

Abstract: Immunological cross-reactions between enteroviruses and islet cell autoantigens have been suggested to play a role in the etiopathogenesis of insulin dependent diabetes mellitus (IDDM). In the nonobese diabetic mouse, an autoimmune model of IDDM, one of the reactive beta cell autoantigens is the heat shock protein 60 (HSP60). These studies were prompted by sequence homology discovered between the immunogenic region in HSP60 and two regions in enterovirus capsid proteins, one in the VP1 protein and the other in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…Polyclonal antisera raised against enteroviruses have been shown to cross react with heat shock protein (hsp)-60 [25] and the tyrosine phosphatase, IA-2 [26]. However, it seems unlikely that the Dako vp-1 antiserum recognised either of these proteins in the beta cells in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Polyclonal antisera raised against enteroviruses have been shown to cross react with heat shock protein (hsp)-60 [25] and the tyrosine phosphatase, IA-2 [26]. However, it seems unlikely that the Dako vp-1 antiserum recognised either of these proteins in the beta cells in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Even though its specificity has been demonstrated in these studies, it has also been shown that antibodies against enterovirus VP1 protein may cross-react with heat shock proteins, especially HSP60 [27]. We studied possible crossreaction by staining the tissue sample using HSP60-specific antibody.…”
Section: Discussionmentioning
confidence: 99%
“…CBV4 and E9 strains isolated in this way have been studied, and attempts to identify diabetic determinants have been made (21,37,48,52). Other studies have identified sequences in enteroviruses that could be involved in autoimmunity through molecular mimicry (13,14,36,53). Recently, enterovirus RNA has been demonstrated in islet cells of some diabetic patients, and these cells were shown to express several receptors recognized by enteroviruses (55).…”
mentioning
confidence: 99%